CORRELATION BETWEEN PARENTING PATTERNS AND INDEPENDENCE IN LEARNING ON LEARNING OUTCOMES TO FOURTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN CLUSTER 2, CIPONDOH SUB-DISTRICT, TANGERANG CITY IN THE ACADEMIC YEAR OF 2019/2020 - Tia Febri Astuti; Muhamad Chamdani; Ratna Hidayah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
AbstractThe study aimed to determine positive correlation between parenting patterns and independence in learning on learning outcomes to fourth grade students of public elementary schools in cluster 2 in Cipondoh Sub-district Tangerang City in academic year of 2019/2020. It was correlational quantitative method. Sampling method was a simple random sampling technique. The researcher used the SPSS application in analyzing regression, multiple correlation, and classical assumption test of data. The results showed that (1) the value of correlation coefficient between parenting patterns on learning outcomes was 0.344 and the determination coefficient was 11.9%; (2) the value of correlation coefficient between independence in learning on learning outcomes was 0.315 and the determination coefficient was 9.97%; (3) the value of correlation coefficient between parenting patterns and independence in learning on learning outcomes was 0.391 and the determination coefficient was 15.3%. It concludes that there is positive correlation between parenting patterns and independence in learning on learning outcomes to fourth grade students of public elementary schools in cluster 2 in Cipondoh Sub-district Tangerang City in academic year of 2019/2020.